The Effects of Robbery in Barangay 171 North, Caloocan City Amidst Pandemic: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to provide initial observations about the effects of robbery during the pandemic. This measure strengthens the position of barangay officials to help fight against robbery amidst the pandemic.  Since the pandemic started, Barangay 171 North Caloocan has suffered from the coronavirus (COVID-19). People lose their job, triggering mental health and the worst thing is to die because of the virus. Barangay 171 North Caloocan City and the support of the whole barangay follow the curfew hours, which help the community during a pandemic to prevent a crime such as robbery and prevent and control the spreading of the virus within their community. This global pandemic can cause different threats to the population, like hunger, unemployment, and financial and mental health. These crises may cause an increase in crimes like robbery. In this study, the researcher aims to determine the effects of robbery in Barangay 171 North Caloocan City amidst the pandemic and to know what the power to adopt the following temporary emergency measures to respond to the crisis brought by the pandemic and also to know the prevention and problems that are affecting to the residence.  The researcher utilized normative, descriptive methods to determine the effects of robbery in Barangay 171, North Caloocan City, amid the pandemic. The researcher’s goal is to employ this method to describe the nature of the real situation as it exists at the time of the study. The questionnaire and interview were used to gather data and information necessary to complete the study.  Despite the pandemic, the researcher interviewed the barangay officials and the Community. Although they are brave warriors against the thief, they welcome the researcher warmly. The main instrument used to gather information to answer the specific problem raised is the questionnaire. In this method, written responses were given to prepared questions intended for the respondents to reply. Questions were translated into Tagalog to ensure the validity of the responses, that is, correct interpretation and understanding by the respondents of the specific item in line with the purpose of the study.  The study concluded that based on the demographic profile of the two groups of respondents, Barangay officials and the community at Barangay 171 North Caloocan City, the majority of the respondents came from the age bracket 18-50 years old, female, single, and married. In the assessment, the Barangay Officials know much about the robbery in Barangay 171 North Caloocan City. As assessed, the Barangay Officials and the community of Barangay 171 North Caloocan moderately agree about the trouble of sleeping among their behaviour, sense of fear in mental health and lack of psychological concentration.  As attested by the respondents, the recommendations proposed by the researchers are to ensure the awareness of robbery cases in Barangay 171 North Caloocan City as highly recommended.  The findings of the study show the implementation, scope, and limitation of the effect of robbery in Barangay 171 North Caloocan City amidst the pandemic that can be used in Barangay 171 to enforce the punishment to the violators of robbery in the Barangay 171 North Caloocan.